THE EFFECTIVENESS OF BLENDED LEARNING APPROACHES IN DEVELOPING FOREIGN LANGUAGE SKILLS IN HIGHER EDUCATION INSTITUTIONS: A THEORETICAL-ANALYTICAL STUDY - Mamurov Sanjarbek Abdunabiyevich (International Journal of Literature and Language Studies, 2026)
This article analyzes the theoretical foundations and practical effectiveness of the blended learning approach, which integrates traditional classroom instruction with digital technologies to develop foreign language (English) skills within the higher education system. Based on a descriptive-analytical (desk-research) methodology, this study conducts a thematic analysis of international research published between 2004 and 2023. It highlights the impact of blended learning on reading, writing, listening, and speaking skills, as well as its contribution to students' academic motivation and autonomy. The findings indicate that while the blended learning model offers several advantages over traditional education, its effectiveness directly depends on technical infrastructure, teacher readiness, and pedagogical design. Finally, practical recommendations have been formulated for higher education institutions in Uzbekistan, specifically for the field of English philology.